2021
DOI: 10.3390/su13168945
|View full text |Cite
|
Sign up to set email alerts
|

Key Competencies for Sustainability in University of Iceland Curriculum

Abstract: Sustainable development is growingly being developed in universities around the world. The United Nations presented eight Sustainability Key Competencies (SKCs) that represent cross-cutting competencies crucial to advance sustainable development and achieve Sustainable Development Goals. The aim of this research is to know to what extent the University of Iceland courses seem to include the emphasis of the SKCs, either in the course description text or the learning outcomes. Data collection took place in early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…This research aimed to understand better student awareness and knowledge on how the SDGs are used in HEIs to motivate students’ learning on sustainability. Just as Pálsdóttir and Jóhannsdóttir (2021) highlighted the importance of the five competencies in their investigation into University of Iceland curriculum, the five competencies are deemed to support a transition toward sustainability. It is essential to consider students’ understanding of sustainability at the end of their studies to understand whether they feel prepared to apply sustainability in their daily work life.…”
Section: Discussionmentioning
confidence: 99%
“…This research aimed to understand better student awareness and knowledge on how the SDGs are used in HEIs to motivate students’ learning on sustainability. Just as Pálsdóttir and Jóhannsdóttir (2021) highlighted the importance of the five competencies in their investigation into University of Iceland curriculum, the five competencies are deemed to support a transition toward sustainability. It is essential to consider students’ understanding of sustainability at the end of their studies to understand whether they feel prepared to apply sustainability in their daily work life.…”
Section: Discussionmentioning
confidence: 99%
“…The study aims to provide guidance to support institutions in the transition process towards sustainability. This research work creates awareness so that higher education institutions can take responsibility and commit more to the SDGs [12,14,18].…”
Section: Discussionmentioning
confidence: 99%
“…The second study by Redman et al structured the field of sustainability competency assessment and provided a criteria-based overview of the currently used tools, through a systematic literature review of 75 studies that detail the use of an assessment tool [17]. Finally, the third study by Pálsdóttir and Jóhannsdóttir identified competencies that should be fostered through university teaching and learning, and showed that twelve key competencies are crucial for sustainable development, including those for systemic thinking, anticipatory thinking, and critical thinking [18].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, educational institutions are realizing the idea of achieving the Sustainable Development Goals (SDGs). It also requires the identification of urgent socio-ecological problems, planning and development of educational programs [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%